The Effect of Using Slang among Students towards the Indonesian Language - Rafiqoh, Aulia (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2023)
Language has evolved along with the times. One of the variations that arise as a result of language development is slang. Slang in Indonesia is widely used by teenagers. The slang also continues to develop over time. The use of slang keeps growing and impacts the original grammatical of the Indonesian language itself. Based on this problem, the researcher attempted to examine the impact of the use of slang among adolescents. The research was conducted using a qualitative descriptive method. The sample was selected using a purposive sampling technique. The data collection technique was done by semi-structured interviews using a voice recorder and small notes. After the data was obtained, the analysis was carried out using a phenomenological approach. The results of data analysis found that the use of slang causes teenagers to be unfamiliar and unable to use Indonesian properly. This makes it difficult to communicate using Indonesian, especially in an educational environment for high school students. In addition, this also disrupts the learning process at school. Based on these results, it can be concluded that the impact of using slang can damage the structure and shift the role of the original Indonesian language.